Why are pediatricians uncomfortable with prescribing emergency contraception for adolescents? - Renata Vieira Amorim; Marco Antônio Barbieri; Camila Bôtto-Menezes; Fábio Carmona; Alexandre Archanjo Ferraro; Heloisa Bettiol (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: Emergency contraception (EC) is an effective and safe method for preventing unplanned pregnancy after unprotected sexual intercourse among adolescents but is infrequently prescribed by pediatricians. Because of the scarcity of data on the discomfort with EC prescription among physicians in Brazil, this study aimed to identify associated factors with discomfort with EC prescription among pediatricians in the state of Amazonas. Methods: A web-based, cross-sectional study including sociodemographic data, knowledge, attitudes, and discomfort with EC prescription was used. Multivariate logistic regression and artificial intelligence methods such as decision tree and random forest analysis were used to identify factors associated with discomfort with EC prescriptions. Results: Among 151 physicians who responded to the survey, 53.0% were uncomfortable with prescribing EC, whereas only 33.1% had already prescribed it. Inexperience was significantly associated with discomfort with EC prescription (odds ratio 4.47, 95% confidence interval 1.71-11.66). Previous EC prescription was protective against discomfort with EC prescription in the three models. Conclusions: EC is still infrequently prescribed by pediatricians because of inexperience and misconceptions. Training these professionals needs to be implemented as part of public health policies to reduce unplanned adolescent pregnancy.